Nonlinear flow-induced vibration response characteristics of a tubing string in HPHT oil&gas well. (January 2021) - Guo, Xiaoqiang; Liu, Jun; Wang, Guorong; Dai, Liming; Fang, Dake; Huang, Liang; He, Yufa
Highlights: A nonlinear FIV model of tubing string in HPHT oil&gas wells was established and verified by similar experiment. The production allocation should be far away from the mutation value which can be determined using the FIV model. In well trajectory design, the length of vertical section should be reduced, the length of building section and the inclination angle should be increased. The optimal position of the packer can be determined using the FIV method to guide the design of it. Abstract: This study has established a nonlinear flow-induced vibration (FIV) model of tubing string by using the micro-element method and energy method with the Hamiltonian variational principle, in order to address the vibration failure problem of the tubing string induced by high-speed fluid flow in the tubing of high temperature and high pressure (HPHT) oil&gas well. This model considered factors such as borehole trajectory changes, wellbore temperature and pressure variations, self-weight of the tubing string, and the contact-impact of the tubing-casing. Based on the structural parameters of the M high-yield gas well in the South China Sea, a simulation experiment of the tubing string vibration was conducted according to the similarity principle. A comparison between the experiment data and theoretical data showed that the calculation accuracy exceeded 84%, which verified the correctness and validity of the nonlinear vibration model established in this study. On this basis, the influence of the production rate, well inclination angle, well section length, and packer position on the vibration response characteristics of the tubing string were analyzed systematically. It was found that: ①with the increase of the production rate, the vibration response of the tubing string became clearer. The production rate interval that showed abrupt changes was from 0.9 1.2 million m 3 /day. Thus, during designing, such production rate intervals with abrupt changes should be avoided to ensure the safe usage of the tubing strings; ②with the increase of the well inclination angle, the vibration response of the tubing string decreased to a certain extent. Regarding the influence of the well section length, the longitudinal vibration response of the tubing string was most sensitive to the length of the vertical section, followed by the steady inclined section, and finally the angle building section. Thus, during designing, the length of the vertical section should be reduced, while the length of the angle building section and the well inclination angle of the steady inclined section should be increased; ③As the position of the production packer moved up, the vibration responses of the lower and middle tubing strings both decreased, and the optimal packer position was between 3, 549 and 3, 666 m. The research results can serve as an effective analysis tool and provide a theoretical basis for the safety design of the tubing strings in the HPHT oil&gas well site.